The Requirement of Spousal Consent for Transfer of Shares in Public Companies under Ethiopian Law: A Call for Free Transferability of Shares - Zeleke, Yihun (Bahir Dar University Journal of Law, 2023)
Due to the increasing importance of shares as means of householdsavings, countries with statutory matrimonial regime incorporate rules,in their family law, that regulate matters related to management andtransfer of shares. Especially, countries with default rule of a communityof matrimonial property require spousal consent for the transfer ofcommon property of spouses, but they exempt such requirement for thetransfer of shares in a commercial company. The position of Ethiopianlaws in this regard is absurd. The practice is mixed, inconsistance andarbitrary. It also creates discord of opinion to the extent of making somecompanies unsure of how to act. This directs the researcher to raise thefollowing questions: Is spousal consent a requirement to transfer sharesof public companies under Ethiopian law? Should spousal consent be arequirement for such transfers? Is there a lesson Ethiopia may draw fromother countries in this regard? Through analysis of these issues, thewriter concludes that the position of Ethiopian law concerning the issueof spousal consent vis-Ã -vis transfer of share is ludicrous and inadequate.This article argues for a clear exemption of the requirement of spousalconsent for the transfer of shares in public companies and recommendsthe country to draw lessons from other countries to realize the freetransferability of shares.